Detection of Excess Presence of 99mTc-MDP Near Injection Site—A Case Report - Crowley, James R.; Barvi, Iryna; Greulich, Debbie; Kiser, Jackson W. (Frontiers in Medicine, 2021)
Nuclear medicine extravasations and prolonged venous stasis may cause poor quality and quantification errors that can affect image interpretation and patient management. Radiopharmaceutical remaining near the administration site means that some portion of the radioactivity is not circulating as required for the prescribed uptake period. This case describes how, without dynamic imaging, immediately detecting excess presence of 99mTc-MDP near the injection site enables the technologist to apply mitigation tactics early in the uptake process. It also suggests that detecting an extravasation or stasis early in the injection process can be important for image interpretation and minimizing radiation dose to tissue.